IMPROVING STUDENTS' HEALTH PREPAREDNESS THROUGH LOCAL WISDOM-BASED DISASTER RISK REDUCTION EDUCATION AT EMAUS ELEMENTARY SCHOOL - Fidiana Kurniawati; Desi Natalia Trijayanti Idris (JTH: Journal of Technology and Health, 2026)
Disaster Risk Reduction (DRR) needs to be introduced early to improve disaster mitigation, especially for special groups. Integration of local wisdom in learning becomes a contextual strategy to improve student preparedness for disasters. Aims to analyze the effect of local wisdom integration in DRR education on improving student preparedness at Emmaus Elementary School. The research method used a pre-experimental design with a pretest–posttest approach. The number of respondents was 33 students whose preparedness levels were measured before and after the intervention using a questionnaire instrument and an observation checklist based on eight preparedness indicators. The results showed that 27 respondents experienced an increase in preparedness after the intervention. Statistical analysis used the Wilcoxon test, that showed p value = 0.001 (p < 0.05) with Z = -4.778, which means there is a significant effect of local wisdom integration in DRR education on student preparedness. This study concludes that the integration of local wisdom is effective in increasing students' preparedness for disasters and can be an innovative approach in disaster education in elementary schools.